Patient Perception for 24 Hours Discharge after Minimal Invasive Gynecological Surgery in Saudi Population - Ahmed Mousa, (Pakistan Journal of Medical & Health Sciences, 2022)
Same day discharge are considered safe and are cost effective in patient with minimal invasive gynecological surgery. Objectives: To evaluate patient perception of 24 hours discharge after minimally invasive gynecological surgery in selective type of patient depended on specific criteria in Saudi population. Methodology: It is a retrospective study conducted at Dr. Soliman Fakeeh Hospital during 1st January 2016 till 30 December 2019, looking for patient perception of 24 hours discharge after minimal invasive gynecological surgery in Saudi population. Results: Excellent health status was observed in 49.1% of the patients, while 34% been in a good status, and 17% with fair level. Age range of 49.1% was between 25 to 34 years. Almost 84.9% respondents were holding a university degree, 9.4%, 3.8%, and 1.9% had high school, elementary, and intermediate degree, respectively. Women living with their children or grandchildren were 66% while 18.9% were living with other family members, 13.2% living with spouse, and only 1.9% were living alone Conclusions: Same day discharges are associated with a better overall prognosis and patient satisfaction. There are specific criteria to be met before a surgeon determines if a patient is fit for same day discharge. The implementation of same day discharge programs would promote economic benefits, better access to surgical care, and overall greater efficacy. Surgeons should be made aware of the better prognostic implications of same day discharges as well as their impact on patient satisfaction